Quantitative 3D analysis of tissue damage in a rat model of microembolization. (9th November 2021) - Georgakopoulou, Theodosia; van der Wijk, Anne-Eva; Bakker, Erik N.T.P.; vanBavel, Ed; Majoie, Charles; Marquering, Henk; van Bavel, Ed; Hoekstra, Alfons; Dippel, Diederik; Lingsma, Hester; van der Lugt, Aad; et al.
Abstract: There is a discrepancy between successful recanalization and good clinical outcome after endovascular treatment (EVT) in acute ischemic stroke patients. During removal of a thrombus, a shower of microemboli may release and lodge to the distal circulation. The objective of this study was to determine the extent of damage on brain tissue caused by microemboli. In a rat model of microembolization, a mixture of microsphere (MS) sizes (15, 25 and 50 µm diameter) was injected via the left internal carotid artery. A 3D image of the left hemisphere was reconstructed and a point-pattern spatial analysis was applied based on G- and K-functions to unravel the spatial correlation between MS and the induced hypoxia or infarction. We show a spatial correlation between MS and hypoxia or infarction spreading up to a distance of 1000–1500 µm. These results imply that microemboli, which individually may not always be harmful, can interact and result in local areas of hypoxia or even infarction when lodged in large numbers.